Randomized Controlled Trial of Treatment Expectation and Intravenous Fluid in Pediatric Migraine. Issue 9 (28th August 2014) - Richer, Lawrence; Craig, William; Rowe, Brian
Abstract : Objective: (1) The primary objectives were (1) to assess the response to intravenous (IV) fluid in children presenting to the ED with migraine and; (2) to assess the effect of treatment expectation on the response to I. Background: Despite a lack of evidence for the practice, many emergency department (ED) migraine treatment protocols include a bolus of IV fluid. This study assessed the overall response to IV fluid hydration and the effect of expected medication treatment on the pain response among children and adolescents with migraine in an urban ED. Methods: A single‐blind, randomized parallel arm trial of 10 mL/kg IV 0.9% sodium chloride for children and adolescents aged 5‐17 years presenting to a pediatric ED with migraine. Patients were randomized into group A (no expectation of medication in combination with IV fluid) and group B (expectation that medication may be given simultaneously). All participants were treated with standard care following the 30‐minute assessment. Results: Forty‐seven participants were randomized and 2 were excluded; mean age was 13.3 years and 31 (67.4%) were females. Demographics and baseline characteristics were similar between groups. Overall, there was no statistically significant difference for the primary outcome – change from baseline on the visual analog scale (VAS) at 30 minutes with a mean change of −12.3 mm (standard deviation [SD] 17.9) in group A and −12.7 mm (SD 13.2) in group B ( P  = .936). The standardized difference between the 2 means (Cohen's d effect size) was low at 0.024 (95% confidence interval [CI] −0.56 to 0.61). Overall, complete headache relief was observed in only 1 participant; 16 of 45 (35.6%; 95% CI 21.8 to 51.2) had a reduction in headache of 33% or more and 8 of 45 (17.8%; 95% CI 6.1 to 29.4%) had a minimum clinical significant difference of 30 mm or more on VAS with 4 in each group. Thirteen of 39 patients with follow‐up data (33.3%; 95% CI 19.1 to 50.2%) reported a moderate or severe headache at the 24‐hour follow up with no difference between groups; only 3 patients returned to the ED. One participant reported a minor IV‐related adverse event. Conclusions: The overall decrease in pain with IV fluid is small and clinically insignificant. Treatment expectation did not significantly influence headache relief at 30 minutes with IV fluid hydration in children or adolescents with migraine in the ED. The average relief of headache with IV fluid alone was small; however, a clinically meaningful response was observed in 17.8%. Recurrence of headache is common in 33% after ED discharge.